Sieci wywiadowcze w świetle analizy sieciowej. Przypadek wywiadu wschodnio-niemieckiego w Skandynawii - Elo, Kimmo (Pamięć i Sprawiedliwość, 2014)
During the Cold War the four Nordic countries – Finland, Sweden, Norway and Denmark – formed an interesting geopolitical area in the European north, characterized by both differences and similarities. Recent studies on the East German foreign intelligence have shown, that the Nordic countries were an important, yet not central operational area, undoubtedly enjoying a different status for the East German foreign intelligence. In this article, East German intelligence activities toward the Nordic countries are used as a case study in order to exemplify how historical network analysis could be used to uncloak new historical knowledge. Despite its close connection to many of the methodological questions and problems related to uncloaking hidden structures or analyzing network dynamics tackled by network analysts in terrorist or criminal studies, researchers on Cold War intelligence has shown only a limited interest in network analysis. This article draws from this disinterest among scholars on Cold war intelligence studies in network analysis and tries to bring upon methodological incentives hopefully encouraging historians to familiarize themselves with the promises and basics of network analysis in order to imagine how network analysis could help them to obtain qualitatively new knowledge. The material used in the empirical analysis consists of database records on Nordic affairs stored in the central information system of the East German foreign intelligence service. The article introduces and exemplifies some powerful network visualization and analysis techniques suitable for uncloaking network-related knowledge from intelligence materials and for critical assessment of the results.